Pengaruh Leverage, Likuditas, Perputaran Modal Kerja dan Inflasi Terhadap Profitabilitas pada Perusahaan Kelapa Sawit yang Terdaftar di Bursa Efek Indonesia Periode 2015-2018 - Christine Refina Malinda Pande; Deannes Isynuwardhana (Universitas Pamulang, 2021)
ABSTRACTOil palm companies are one of the sectors that have an impact on the economy. Indonesia has a climate that is very suitable for planting oil palm. The company's goal is to make a profit. Then the company will improve its financial performance in order to achieve its goals. Basically, the goal of the company is to be able to increase the company's profitability. The company's profitability will reflect a company's financial condition, and illustrate the effectiveness and efficiency of the company in managing its operations. The purpose of this study is to determine the significant effect of leverage, liquidity, working capital turnover, and inflation that affect the profitability of oil palm companies listed on the Indonesia Stock Exchange in the 2015-2018 period with a large sample of 11 companies. The results of the study with panel data analysis using the E-views 9 application. The data collection method used a secondary data source in the form of an annual financial report document. Based on the research results, it is found that simultaneously leverage, liquidity, working capital turnover, inflation have an effect on profitability. Partially leverage, liquidity has a positive effect on profitability, and working capital turnover, inflation has no effect on profitability.